Short Communication: Biodiversity of the Gaga chicken from Pinrang, South Sulawesi, Indonesia based on the bioacoustic analysis and morphometric study (Biodiversitas Journal of Biological Diversity, 2017)
Abinawanto, Effendi PS. 2017. Biodiversity of the Gaga chicken from Pinrang, South Sulawesi, Indonesia based on the bioacoustic analysis and morphometric study. Biodiversitas 18: 1618-1623. Gaga chicken (Gallus gallus domesticus) is the local ornamental chicken originated from South Sulawesi, Indonesia, being kept for the crows. Gaga chicken which also called â€œayam ketawaâ€ (â€œlaughing chickenâ€) has the unique crowing song, which sounds like human laughing. Gaga chicken which has long and fast crowing song is called â€˜dangdutâ€™ type, while the short and slow crowing song is named â€˜slowâ€™ type. The objective of present study is to investigate the biodiversity of Gaga chicken from Pinrang, South Sulawesi, Indonesia based on morphometric and bioacoustic characters. Twenty samples of Gaga chicken have been collected, consisted of eight â€˜slowâ€™ types and twelve â€˜dangdutâ€™ types, respectively. Data were analyzed by t-test using SPSS ver. 22. The result showed that â€˜slowâ€™ type was bigger than â€˜dangdutâ€™ type. Morphometric characters could be applied to determine the biodiversity of Gaga chicken.
Keywords: Ayam ketawa; crowing song; Gaga chicken; morphometric